Fatigue life prediction for parallel-wire stay cables considering corrosion effects. (September 2018) - Lan, Chengming; Xu, Yang; Liu, Caiping; Li, Hui; Spencer, B.F.
Highlights: Fatigue experiments are conducted/reported for corroded high strength steel wire. The quantitative influence of corrosion on the fatigue life of steel wire is evaluated. Corrosion and fatigue life relations for parallel-wire stay cables are established. Short fatigue life wires are found to dominate the fatigue life of stay cables. Corrosion effects in wires are more pronounced for lower stress ranges. Abstract: Corrosion in stay cables of long-span cable-stayed bridges is a severe problem. This paper studies the quantitative influences of corrosion on fatigue life for parallel-wire stay cables. First, accelerated corrosion tests were conducted using acetic acid salt spray (AASS) for exposure periods from 1 d to 60 d; subsequently, a multi-parameter Weibull model for corrosion-stress-life (C-S-N) is employed to describe the influence of corrosion on fatigue life of such steel wires. Fatigue damage evolution models of multi-step loading are then used to establish recursion formulas for the probabilistic character of the fatigue life of parallel-wire stay cables. Monte Carlo simulation (MCS) is conducted to simulate the fatigue life of the stay cable, assuming load redistribution after the failure of each wire. Results indicate that the fraction of wires with short fatigue lives dominates the fatigue life of stay cable. Corrosion effects on fatigue life for both steel wire and stay cables are nearly the same. Although the variance of fatigue life of stay cable is much smaller than that of the steel wire, the fatigue performance of the stay cable becomes stable. The fatigue life of stay cable decreases significantly, as the corrosion degree of the steel wire increases, especially, in the lower stress ranges. Therefore, to prevent premature fatigue failures of parallel-wire stay cables, avoiding corrosion in the steel wires during the in-service period is crucial.